Analysis of regional electricity demand for Turkey - Gülsüm Akarsu (Regional Studies, Regional Science, 2017)
Electricity sectors have experienced a transformation towards more liberalized and decentralized structure since the 1980s. This transformation process increases the importance of regional-level analysis. This study analyses the factors affecting regional electricity demand. As a case study, analysis is performed for Turkey by employing a dynamic spatial lag panel data model. The model allows for the inclusion of spatial interaction effects into the analysis which are important but mostly ignored in the literature. Findings show evidence of spatial spillover effects. Therefore, the paper concludes that one should consider spatial spillover effects of economic factors and regional energy policies.